Manufacturing A Fiber Optic Based Trainer Module Using The Star Topology Method Using Optical Distribution Point (Odp) And Optical Termination Box (Otb) - Nilna, Mellya Gusriva; Asril, Aprinal Adila; Lifwarda, Lifwarda (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2025)
Optical fiber is a transmission medium made from glass that is used to transmit information in the form of light. As time goes by, the need for fast telecommunications services in data exchange is increasing. However, there are problems with optical fibers such as high attenuation or connection errors that interfere with performance. In this final project, a trainer module was designed regarding splicing and measuring fiber attenuation to help students understand how to connect optics properly and correctly. This module uses devices such as ODP and OTB which are connected to each other. The research results show that the highest attenuation measured was 20.15 dB, while the lowest attenuation value was 0.29 dB. Attenuation corresponding to the calculated link budget of 1.7605 dB indicates good results, while high attenuation indicates poor quality.